Azo reductase activity of intact Saccharomyces cerevisiae cells is dependent on the Fre1p component of plasma membrane ferric reductase - Ramalho, Patrícia A. (2005)
Unspecific bacterial reduction of azo dyes is a process widely studied in correlation with the biological treatment of coloured wastewaters, but the enzyme system associated with this bacterial capability has never been positively identified. Several ascomycete yeast strains display similar decolourising behaviours. The yeast-mediated process requires an alternative carbon and energy source and is independent of previous exposure to the dyes. When substrate dyes are polar, their reduction is extracellular, strongly suggesting the involvement of an externally directed plasma membrane redox system. The present work demonstrates that, in Saccharomyces cerevisiae, the ferric reductase system participates in the extracellular reduction of azo dyes. The S. cerevisiae deltafre1 and deltafre1deltafre2 mutant strains, but not the deltafre2 strain, showed a much-reduced decolourising capabilities. The FRE1 gene complemented the phenotype of S. cerevisiae deltafre1 cells, restoring the ability to grow without externally added iron and to decolorize the dye, following a pattern similar to the one observed in the wild-type strain. These results suggest that under the conditions tested, Fre1p is a major component of the azo reductase activity.